Riociguat for chronic thromboembolic pulmonary hypertension and pulmonary arterial hypertension: a phase II study - Ghofrani, Hossein Ardeschir; Höper, Marius; Halank, Michael; Meyer, Franz Joachim; Stähler, Gerd; Behr, J.; Ewert, Ralf; Weimann, G.; Grimminger, Friedrich (The European respiratory journal, 2010)
We assessed the therapeutic potential of riociguat, a novel soluble guanylate cyclase stimulator, in adults with chronic thromboembolic pulmonary hypertension (CTEPH; n = 42) or pulmonary arterial hypertension (PAH; n = 33) in World Health Organization (WHO) functional class II/III. - In this 12-week, multicentre, open-label, uncontrolled phase II study, patients received oral riociguat 1.0-2.5 mg t.i.d. titrated according to systemic systolic blood pressure (SBP). Primary end-points were safety and tolerability; pharmacodynamic changes were secondary end-points. - Riociguat was generally well tolerated. Asymptomatic hypotension (SBP <90 mmHg) occurred in 11 patients, but blood pressure normalised without dose alteration in nine and after dose reduction in two. Median 6-min walking distance increased in patients with CTEPH (55.0 m from baseline (390 m); p<0.0001) and PAH (57.0 m from baseline (337 m); p<0.0001); patients in functional class II or III and bosentan pre-treated patients showed similar improvements. Pulmonary vascular resistance was significantly reduced by 215 dyn·s·cm−5 from baseline (709 dyn·s·cm−5; p<0.0001). 42 (56%) patients were considered to have experienced drug-related adverse events (AEs; 96% mild or moderate). Dyspepsia, headache and hypotension were the most frequent AEs. Study discontinuation because of AEs was 4%. - These preliminary data show that riociguat has a favourable safety profile and improves exercise capacity, symptoms and pulmonary haemodynamics in CTEPH and PAH. Randomised controlled trials are underway.
Gesehen am 07.03.2023